Dehydration of fructose to 5-hydroxymethyl furfural over ordered AlSBA-15 catalysts - Lucas, Nishita; Kokate, Ganesh; Nagpure, Atul; Chilukuri, Satyanarayana V. (Microporous and Mesoporous Materials, 2013)
5-Hydroxymethyl furfural is an important platform chemical. It is successfully synthesized from renewable carbohydrates using mesoporous AlSBA-15 catalysts under biphasic conditions. Fine tuning of the catalyst acidity is important to drive the reaction to give good yields of furan compound. Al-SBA-15 catalysts with different Si/Al ratios were prepared and characterized by XRD, Al-27 MASNMR, SEM, TEM, N-2 sorption, ICP-OES and TPD of ammonia. Results show that part of aluminium is substituted into tetrahedral positions. The catalyst with lower acid site density but medium to strong acid strength favours selective formation of HMF. Under the optimized conditions, HMF selectivity was as high as 88% at 59 mol% conversion of fructose. Leaching of part of aluminium occurs under hydrothermal conditions, if solvent mixtures containing water are used, while activity can be retained if DMSO is used as solvent. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acidity; AlSBA-15; dehydration; fructose; Hydroxymethyl furfural

Novel catalysts for valorization of biomass to value-added chemicals and fuels - Lucas, Nishita; Kanna, Narasimha Rao; Nagpure, Atul S.; Kokate, Ganesh; Chilukuri, Satyanarayana V. (Journal of Chemical Sciences, 2014)
Key furan compounds such as 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA) and 2,5-dimethylfuran (DMF) were synthesized from renewable feedstocks. Dehydration of fructose was carried out in biphasic conditions employing several solid acid catalysts by targeting selective formation of HMF. Its selectivity is linearly dependent on total acidity clearly revealing that lower acidity favours selective formation of HMF. Oxidation and hydrogenolysis of HMF has been explored using 2 wt% Ru-K-OMS-2. The catalysts used for each transformation were subjected to detailed characterization using XRD, BET surface area, temperature-programmed desorption and transmission electron microscopy. The effect of various reaction parameters was also investigated for obtaining high yields of desired chemical intermediates. High FDCA yields of 93.4 mol% and 66 mol% were achieved in alkaline and base-free conditions, respectively. The 2 wt% Ru-K-OMS-2 is a versatile catalyst as it also catalyses HMF hydrogenolysis giving 33 mol% of DMF. Thus, utility of various novel materials as catalysts has been demonstrated in the multistep transformations of hexoses to furan-based fuels and chemicals.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: 2; 5-dimethylfuran; 5-furan dicarboxylic acid; 5-hydroxymethyl furfural; dehydration; fructose

Manganese increases high mannose glycoform on monoclonal antibody expressed in cho when glucose is absent or limiting: implications for use of alternate sugars - Surve, Tanaya; Gadgil, Mugdha (Biotechnology Progress, 2015)
Alternate sugars such as galactose and fructose are metabolized at a slower rate than glucose and result in lower accumulation of lactate. While low lactate accumulation is desirable, we report that complete substitution of glucose with these sugars results in an increase in M5 high mannose glycans. Surprisingly, this increase is much higher when the culture is supplemented with manganese: for example, when cells are cultured with galactose, M5 high mannose glycan content increased from 5% at 1 nM Mn2+ in the basal medium to 32% with 16 mu M Mn2+ supplementation. When galactose is supplemented with glucose maintained at low concentrations, a small reduction in high mannose glycans is seen. In control cultures with glucose, the high mannose content was however <2% in this range of Mn2+ concentration. By varying Mn2+ and glucose supplementation levels, with or without galactose, we systematically demonstrate that Mn2+ concentration and glucose availability, together, significantly affect the high mannose glycan content. To our knowledge, this is the first report that shows that the effect of Mn2+ on high mannose glycan content depends on glucose availability. At each Mn2+ supplementation level evaluated, galactosylation percentages were highest for cultures where galactose was supplemented with glucose at non-limiting concentration. (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:460-467, 2015
Keywords: CHO; fructose; galactose; glucose; glycosylation; high-mannose glycan; manganese

Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Highly efficient zirconium based carbonaceous solid acid catalyst for selective synthesis of 5-HMF from fructose and glucose in isopropanol as a solvent - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2022)
A new zirconium based carbonaceous solid acid catalyst Zr@CC-PA with both Lewis and Bronsted acidic sites was prepared by simultaneous carbonization and phosphonation of glucose followed by incorporation of zirconium metal on the surface of the catalyst. The catalyst was easy to prepare and the synthesized catalyst was well characterized using different techniques such as FT-IR, P-XRD, EDAX, SEM, TEM and XPS analysis. The catalytic activity was evaluated for synthesis of a very important platform chemical 5-HMF from fructose to glucose using isopropanol as a solvent. The catalyst was found to be highly efficient giving 86% yield of 5-HMF from fructose and 45% yield from glucose with high selectively. The catalyst can be reused at least four times without depreciation in its catalytic activity. The catalytic method developed is efficient, green and economical.
Keywords: 5-Hydroxymethylfurfural; fructose; glucose; Zirconium based

Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5

Early and advanced glycation end product analysis from women with PCOS on metformin - Ambekar, Aditi S.; Naredi, Nikita; Malakar, Dipankar; Vashum, Y.; Misra, Pratibha; Kulkarni, Mahesh (Reproductive Biology, 2025)
In this cross-sectional study, we have analyzed advanced glycation end products (AGEs) in the plasma and follicular fluid of women with polycystic ovary syndrome (PCOS) taking metformin during in vitro fertilization (IVF) and control women undergoing IVF. Glucose, fructose, fructosamine, carboxymethyl lysine/ arginine (CML/R) proteins, and pentosidine were measured in the plasma and paired follicular fluid. Glycated proteins were characterized by mass spectrometry. Fasting serum glucose and fructosamine were comparable; however, follicular fluid glucose and fructosamine were higher in the PCOS group, and other AGEs remained unaltered. Fructose was lower in both serum and follicular fluid from the PCOS group. A positive correlation between some of these AGEs and sugars estimated was observed. Glucose and fructosamine in the follicular fluid correlated with the antral follicle count. The number of glycated peptides identified in the PCOS group by mass spectrometry was more. Glycated K75, K402 amino acid residues of albumin were detected in the PCOS group only. Additionally, some proteins involved in steroidogenesis and oocyte maturation as well as transporters, and extracellular matrix proteins, were found to be glycated in the PCOS group, which may affect their function. Elevated glucose and fructosamine in the follicular fluid of the PCOS group may contribute to abnormal folliculogenesis. The glycation of albumin should be validated in more samples to be considered as a marker for PCOS diagnosis.
Keywords: Carboxymethyl lysine; Fructosamine; fructose; glucose; Pentosidine; Polycystic ovary syndrome